Cutibacterium spp. Infections after Instrumented Spine Surgery Have a Good Prognosis Regardless of Rifampin Use: A Cross-Sectional Study - Susana Núñez-Pereira; Eva Benavent; Marta Ulldemolins; Beatriz Sobrino-Díaz; José A. Iribarren; Rosa Escudero-Sánchez; María Dolores Del Toro; Andrés Nodar; Luisa Sorli; Alberto Bahamonde; Helem H. Vilchez; Oriol Gasch; et al. (MDPI AG, 2023)
Infection after spinal instrumentation (IASI) by Cutibacterium spp. is being more frequently reported. The aim of this study was to analyse the incidence, risk factors, clinical characteristics, and outcome of a Cutibacterium spp. IASI (CG) compared with non-Cutibacterium IASI (NCG) infections, with an additional focus on the role of rifampin in the treatment. All patients from a multicentre, retrospective, observational study with a confirmed IASI between January 2010 and December 2016 were divided into two groups: (CG and NCG) IASI. Baseline, medical, surgical, infection treatment, and follow-up data were compared for both groups. In total, 411 patients were included: 27 CG and 384 NCG. The CG patients were significantly younger. They had a longer median time to diagnosis (23 vs. 13 days) (p = 0.025), although 55.6% debuted within the first month after surgery. Cutibacterium patients were more likely to have the implant removed (29.6% vs. 12.8%; p = 0.014) and received shorter antibiotic regimens (p = 0.014). In 33% of Cutibacterium cases, rifampin was added to the baseline therapy. None of the 27 infections resulted in treatment failure during follow-up regardless of rifampin use. Cutibacterium spp. is associated with a younger age and may cause both early and late IASIs. In our experience, the use of rifampin to improve the outcome in the treatment of a Cutibacterium spp. IASI is not relevant since, in our series, none of the cases had therapeutic failure regardless of the use of rifampin.